THE ROLE OF COACHES AND PARENTS IN YOUTH FOOTBALL TRAINING - János TÓTH Jr; Simon BALÁZS (Cluj University Press, 2023)
Our topic is the investigation of the influence of parents and coaches of youth soccer children on the children's sports performance, what is the role of coaches in teams of different youth age groups (according to the physiological effects of children), the relationship between coaches and parents, the relationship between coaches and players, the control and development of the most talented players. With our chosen topic, we set myself the goal of examining whether the support and help of parents or coaches has a greater effect on the child's sports performance. We chose this topic because we would like to help during the coaching career in the future, and we also consider it important to develop the skills of young Hungarian football talents, in which parents and coaches have an important and outstanding role. In our article, we would like to reveal what are the outstanding factors that most influence a player's performance on the field, and to what extent coaches and parents contribute to this. We think that it is important for both sides to see their role in the development of football talent. We would also like to examine to what extent parents contribute to the advancement of their child's soccer career, whether they recognize the factors in which they should help their child progress in soccer. After all, in our opinion, without parental support, it will be more difficult for the player to progress, who will also be more balanced emotionally, which also has a significant impact on his sports performance, if the parent monitors and encourages him during his football career. Do soccer coaches consider their relationship with their students important? What is the role of football coaches in the different youth age groups, what is the focus? To what extent does the role and education of parents influence their children's performance, football coaches, how can they cooperate with parents and players? How can football coaches keep under control and develop the most talented child? Received 2023 May 23; Revised 2023 June 15; Accepted 2023 June 16; Available online 2023 July 30; Available print 2023 August 30.